Kajian Kebijakan dan Program Peningkatan Ekonomi Lokal Di Kabupaten Minahasa Selatan - Pio, Riane Johnly (JURNAL ILMU ADMINISTRASI (JIA), 2012)
Abstract. This study aims to determine the regulations and policies relating to the activities of Small Business, small business contribution to economic growth since the autonomy to implement, and support for small business development in South Minahasa regency. This study used a survey technique, with a population of small businesses in South Minahasa regency. Sample was determined by 30 small business units in six districts with a proportional amount specified villages. While institutions in the survey who had close links with the coaching and development of small businesses. The results indicate the regulations and policies related to various economic activities, more people includes regulations related to the effort to obtain and increase local revenue. Small business enough to contribute to economic growth, particularly in moving the economy to fulfill the basic needs. Realization of government assistance for small business development is still lacking. Although the natural resources in the South Minahasa district has good potential as a driver economic capital, but if not managed wisely hard drives the local economy. Regulations relating to wider access for small business development must be accommodated and encouraged.Â Â Keywords: Local Autonomy, Local Economy, Small Business